GMMA-Based Vaccines: The Known and The Unknown - Mancini, Francesca; Micoli, Francesca; Necchi, Francesca; Pizza, Mariagrazia; Berlanda Scorza, Francesco; Rossi, Omar (Frontiers in Immunology, 2021)
Generalized Modules for Membrane Antigens (GMMA) are outer membrane vesicles derived from Gram-negative bacteria engineered to provide an over-blebbing phenotype, which represent an attractive platform for the design of affordable vaccines. GMMA can be further genetically manipulated to modulate the risk of systemic reactogenicity and to act as delivery system for heterologous polysaccharide or protein antigens. GMMA are able to induce strong immunogenicity and protection in animal challenge models, and to be well-tolerated and immunogenic in clinical studies. The high immunogenicity could be ascribed to their particulate size, to their ability to present to the immune system multiple antigens in a natural conformation which mimics the bacterial environment, as well as to their intrinsic self-adjuvanticity. However, GMMA mechanism of action and the role in adjuvanticity are still unclear and need further investigation. In this perspective, we discuss progresses in the development of the GMMA vaccine platform, highlighting successful applications and identifying knowledge gaps and potential challenges.